(3GdfXGe GdbGfhfi deSFhdjI GdeMce (B: s (3OQGSI ebGQfI (B/ s - (3SYhO WGdH SYhO Ydi GdfZjeTs; (3SGei YHOGdHGbi CHhUGdM s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3JJchf GdQSGdI ef ebOeI h aUd JegjOi h HGHjf hNGJeg h Cge GdfJGFL h GdJhUjGJ GdJj JhUdJ EdjgG GdOQGSI(B: (3aVdkG Yf bGFeI eQGLY HGddZI GdYQHjI h GdCLfHjI(B. (3GdaUd GdJegjOj(B: (3YGdL gPG GdaUd eSGFd eJYOOI cJegjO ddQSGdI h JYQja GdYOjO ef GdCehQ GdeJYdbI HGdQSGdI h bSe GdHGMK GdaUd GdJegjOj Edj KdGKI eHGMK(B: (3JfGhd aj GdeHMK GdChd(B: (3SdWGJ h Mbhb h GdJRGeGJ GdeMce(B: (3NUU GdeWdH GdChd dSdWGJ GdeMce hGdJj YGdLgG aj KdGKI aQhY(B: (3NUU GdaQY GdChd dOQGSI SdWGJ GdeMce aj EUOGQ GdCeQ HGdZQGeI GdJgOjOjI(B: (3HjfeG NUU GdaQY GdKGfj dOQGSI SdWGJ GdeMce aj GdCeQ HGdELQGAGJ GdJMaXjI h GdhbJjI(B: (3HjfeG NUU GdaQY GdKGdK dOQGSI SdWGJ GdeMce aj GSJOYGA GdTghO(B. (3GdHGH GdChd(B: (3hYGdL gPG GdHGH GdQbGHI GdbVGFjI Ydj Yed GdeMce(B: (3h bGe GdHGMK HJbSje gPG GdHGH Edj aUdjf JfGhd aj GdaUd GdChd GdQbGHI GdbVGFjI GdSGHbI Ydj Yed GdeMce aj NeSI eHGMK NUU GdeHMK GdChd dOQGSI GdQbGHI GdbVGFjI Ydj JYjjf GdeMce(B: (3QbGHI GdbVGA Ydj GdJYjjf GdGNJjGQj ddeMce(B: (3h NUU GdeHMK GdKGfj dOQGSI QbGHI GdbVGA Ydj QO GdeMce hGdMGdGJ GdJj dG jLhR ajgG JbOje WdH QO GdeMce(B: (3aVdkG Yf GdVhGHW GdehVhYjI h GdELQGFjI dQO GdeMce(B. (3GdHGH GdKGfj(B: (3YGdL gPG GdHGH eSFhdjI GdeMce h WQb JCejfgG h bSe GdHGMK GdHGH Edj aUdjf JfGhd aj GdaUd GdChd(B: (3UhQ eSFhdjI GdeMce(B: (3h GdJj GJNPJ UhQ eNJdaI ef GdeSFhdjI GdLfGFjI(B: (3GdeSFhdjI GdJCOjHjI(B: (3GdeSFhdjI GdeOfjI(B. (3JfGhd GdeHMK GdChd GdeSFhdjI GdLfGFjI ddeMce aj SJI eWGdH(B: (3YGdL GdeWdH GdChd LQjeI GdQThI(B: (3h YGdL GdeWdH GdKGfj LQjeI GdGNJdGS(B: (3YGdL GdeWdH GdKGdK LQjeI EaTGA GdeYdheGJ(B: (3YGdL GdeWdH GdQGHY LQjeI GdJRhjQ h GSJYeGd eMQQ eRhQ(B: (3HjfeG YGdL GdeWdH GdNGeS LQjeI ZSjd GdCehGd(B: (3h YGdL GdeWdH GdSGOS h GdCNjQ GdGJUGdGJ GdeTHhgI GdeMce eY CWQGa NUheI GdJMcjes
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQi, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B594-640s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdeMces; (3GdeSFhdjI GdLfGFjIs; (3GdeSFhdjI GdeOfjIs; (3SdWGJ GdeMces; (3Mbhb GdeMces; (3SjQ GdNUheg GdJMcjejg s; (3GdeSFhdjg GdeOfjg s; (3GdeSFhdjg GdLfGFjg s; (3eSFhdjg eDSSGJ GdJMcjes; (3GMcGe GdJMcje s; (3GdQbGHg GdbVGFjg GdSGHbg Ydi Yed GdeMce s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs